Relationship between family support with self-care adherence among tuberculosis patients - Falah, Miftahul; Bin Sansuwito, Tukimin; III Dioso, Regidor; Lismayanti, Lilis; Pamela Sari, Nina; Himatul Aliyah, Ima (University of Muhammadiyah Semarang, 2024)
TB is the number one cause of mortality among infectious diseases and the 3rd cause of mortality after heart disease and acute respiratory diseases in Indonesia. The aim of this study was to find a relationship between family support and self-care adherence among tuberculosis patients. The study used quantitative with a cross-sectional method. The population in this study were 55 TB sufferers who were undergoing treatment in 2024 at the Tamansari Public Health Center. The sample for this study was all TB patients recorded in 2024, as many as 55 people, total sampling used in this study. This study was conducted at the Tamansari Public Health Center, Tasikmalaya City. The result showed that the Chi-Square statistical test obtained a p-value of 0.005 (<0.05), and there were significant differences between family support and self-care adherence among tuberculosis patients. In conclusion, there was a relationship between family support and self-care adherence in patients suffering from tuberculosis. Hope for the future study to optimize of family support among families with TB to prevent of TB resistance.